Contribuição ao estudo do gerador de indução duplamente alimentado: operação durante distúrbios na rede elétrica - Costa, Jean Patric da (2010)
The Doubly Fed Induction Generator (DFIG) is one of the most frequently deployed large grid connected Wind Turbines (WT) concept. The implementation of classical vector control techniques, have been proven to work well for considering the initial grid code requirements. However, recently many grid operators are requiring WT to remain connected during grid faults, resulting in low voltage fault ride through capability (LVRT). In addition, it is required for WTs to contribute with reactive support during the fault. As a result, the improvements of the transient behavior of the DFIG, the power converter protection and the controller design have become a challenge for WT manufactures. This work presents a high performance stationary frame non-linear controller for doubly fed induction generator, which improves the steady state and transient behavior of the grid connected wind turbines especially under unbalance voltage dips resulting from network unbalance faults. A controller design procedure that guarantees the DFIG stability under uncertainties and disturbances at grid side is presented in details. Furthermore, it is demonstrated in the thesis that with the proposed controller different goals such as control of grid side active and reactive power, minimization of torque pulsation under unbalance operation and improvement of the low voltage ride through capability can be easily achieved. Simulations and experimental results are given to illustrate the good performance of a grid connected DFIG with the proposed controller.